High-strength low-elongation bipolar current collector and preparation method thereof

By adopting five-layer structure design and cross-link modification processing technology in bipolar current collectors, the curling, pinhole and short circuit problems in the preparation and application of bipolar current collectors are solved, and the high-strength and low-elongation bipolar current collectors are achieved, which improves the safety performance and processing performance of the battery.

CN119725547AActive Publication Date: 2025-03-28YANGZHOU NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411921228.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

During the preparation and application of existing bipolar current collectors, there are problems such as curling of the pole sheet, poor alignment, high elongation, resulting in warping, MD marks, and wrinkles, and pinholes are prone to forming channels through the positive and negative electrodes, resulting in short circuit of the battery.

Method used

A high-strength, low-elongation bipolar current collector design with a five-layer structure, including aluminum layer, base layer I, polymer film layer, base layer II and copper layer, is prepared by cross-linking modification treatment and heating and pressing technology to ensure the strength and stability of the polymer film layer.

Benefits of technology

Effectively prevent pole sheets from curling and pinhole formation, improve battery safety and processing performance, reduce elongation, and improve the overall performance of bipolar current collectors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725547A_ABST
    Figure CN119725547A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of current collectors, in particular to a high-strength low-elongation bipolar current collector and a preparation method thereof. The high-strength low-elongation bipolar current collector is of a five-layer structure and sequentially comprises an aluminum layer, a base coat I, a polymer film layer, a base coat II and a copper layer. The preparation method comprises the following steps: carrying out crosslinking modification treatment on a polymer film I and a polymer film II, sequentially depositing a base coat I and an aluminum layer on the surface of one side of the polymer film I, sequentially depositing a base coat II and a copper layer on the surface of one side of the polymer film II, and finally bonding the surfaces of the other sides, which are not subjected to deposition treatment, of the polymer film I and the polymer film II through heating and pressing. The bipolar current collector prepared by the invention has excellent tensile strength, elongation and thermal shrinkage, effectively avoids penetrating pinholes possibly generated by a single-layer film, basically eliminates the problem of positive and negative electrode short circuit caused by the current collector, and has better application advantages.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of current collectors, and in particular to a high-strength and low-elongation bipolar current collector and a preparation method thereof. Background Art

[0002] Composite current collectors provide a new breakthrough for the development of existing lithium batteries. Composite current collectors can improve the safety performance of lithium batteries and increase the energy density of lithium batteries. Due to the reduced use of metals, composite current collectors also have potential cost advantages. Based on the special characteristics of composite current collectors, a new bipolar current collector has recently emerged. The difference between bipolar current collectors and traditional composite current collectors is that the metal layers on both sides of the base film are respectively an aluminum layer that acts as a positive current collector and a copper layer that acts as a negative current collector. The base film layer in the middle is equivalent to the separator layer of a traditional battery, which serves to isolate the positive and negative electrodes from short circuits.

[0003] Bipolar current collectors can achieve higher power output by shortening the current transmission path and reducing internal resistance, while providing more space for active materials and improving energy density. In addition, the bipolar current collector structure can realize series connection within the battery cell, enabling the single cell to achieve high voltage output.

[0004] At present, the lithium battery industry is still in the early stages of research on bipolar current collectors, and the preparation and application of bipolar current collectors are still immature. There are also the following defects: (1) The metal layer and active material layer on both sides of the base film of the bipolar current collector pole piece are different. There are differences in the compaction and extension of the materials on both sides during the rolling process, which will cause different internal stresses on both sides of the base film, causing the pole piece to curl and poor alignment; (2) Bipolar current collectors with traditional polymer materials as the substrate are prone to warping, MD lines, wrinkles, etc. due to their high elongation under the influence of coating tension and baking zone temperature; (3) Bipolar current collectors are mostly prepared by physical deposition methods, which leads to pinholes in the middle polymer layer during the production process, forming channels that penetrate the positive and negative electrodes, causing battery short circuits.

[0005] Based on this, the present invention will provide a high-strength and low-elongation bipolar current collector and a preparation method thereof, which is of great significance. Summary of the invention

[0006] The object of the present invention is to provide a high-strength and low-elongation bipolar current collector and a preparation method thereof, so as to solve the problems raised in the prior art.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] A high-strength and low-elongation bipolar current collector is divided into a five-layer structure, which is sequentially arranged to include: an aluminum layer, a primer layer I, a polymer film layer, a primer layer II, and a copper layer; the polymer film I and the polymer film II are cross-linked and modified, and then the primer layer I and the aluminum layer are sequentially deposited on the surface of one side of the polymer film I, and the primer layer II and the copper layer are sequentially deposited on the surface of one side of the polymer film II, and finally the polymer film I and the other side of the polymer film II that have not been deposited are bonded by heating and pressing to obtain the obtained bipolar current collector.

[0009] Furthermore, the method for preparing the high-strength and low-elongation bipolar current collector specifically comprises the following steps:

[0010] S1: Preparation of single-sided aluminum layer-composite current collector:

[0011] S11. A layer of a base layer I is deposited on one side of the polymer film I by a physical deposition method;

[0012] S12. A layer of aluminum is deposited on the surface of the base layer I by vacuum evaporation to obtain a single-sided aluminum layer - composite current collector;

[0013] S2: Preparation of single-layer copper layer-composite current collector:

[0014] S21. Depositing a layer of bottom layer II on one side of the polymer film II by a physical deposition method;

[0015] S22. A copper layer is deposited on the surface of the base layer II by water electroplating to obtain a single-sided copper layer-composite current collector;

[0016] S3: The surfaces of the single-sided aluminum layer-composite current collector and the single-sided copper layer-composite current collector that have not been deposited are bonded to each other, and the surfaces are heated and pressed to obtain a high-strength and low-elongation bipolar current collector.

[0017] Furthermore, the physical deposition method in the present invention includes but is not limited to any one of magnetron sputtering and vacuum evaporation.

[0018] Preferably, if the physical deposition method is magnetron sputtering, the process parameters of the magnetron sputtering are: vacuum degree ≤ 1×10 -2 Pa, the sputtering power is 0.5-2KW; if the physical deposition method is vacuum evaporation, the process parameters of the vacuum evaporation are: vacuum degree ≤1×10 -2 Pa, the evaporation temperature is 1400~1600℃.

[0019] Furthermore, the polymer film I and the polymer film II are both subjected to cross-linking modification treatment before physical deposition;

[0020] The cross-linking modification treatment method is: immersing the polymer film I and / or polymer II in an organic solution of a cross-linking agent, immersing for 15 to 90 seconds at 20 to 60° C., taking out, and drying to complete the cross-linking modification treatment.

[0021] Since the polymer film has a low thickness and swells slightly in organic solvents, small molecule cross-linking agents can penetrate into the interior of the molecular chain, resulting in uniform modification of the polymer film.

[0022] Furthermore, the types of the polymer film I and the polymer film II include but are not limited to any one of polypropylene film, polyethylene film, polyethylene terephthalate film, polyimide film, polyphenylene sulfide film, and polystyrene film; and the thickness thereof is 3 to 20 μm.

[0023] Furthermore, the crosslinking agent is a low-temperature crosslinking agent, specifically including but not limited to any one of an organic peroxide crosslinking agent and a multifunctional acrylate crosslinking agent;

[0024] The organic peroxide cross-linking agent includes but is not limited to dicumyl peroxide and di-tert-butyl peroxide;

[0025] The multifunctional acrylate crosslinking agent includes but is not limited to trimethylolpropane triacrylate.

[0026] Furthermore, the parameters of the polymer film II and the polymer film I and the cross-linking agent used in the cross-linking modification treatment may be different.

[0027] Furthermore, the material of the base layer I is metal or metal oxide, specifically including but not limited to any one of aluminum oxide, chromium oxide, and chromium, and its thickness is 1 to 20 nm.

[0028] Furthermore, the process parameters of the vacuum evaporation are: vacuum degree ≤ 1×10 -2 Pa, evaporation temperature is 1400~1600℃

[0029] Furthermore, the thickness of the aluminum layer is 0.5-2 μm.

[0030] Furthermore, the material of the base layer II is metal, specifically including but not limited to one or a combination of nickel, chromium, and copper, and its thickness is 5 to 40 nm.

[0031] Furthermore, the process parameters of the water electroplating are: copper sulfate concentration is 180-220 g / L, current density is 2.5-3.5 A / dm 2 , voltage is 8~12V, temperature is 45~55℃.

[0032] Furthermore, the copper layer has a thickness of 0.5 to 2 μm.

[0033] Furthermore, the process parameters of the heating and pressing are: temperature of 60-150° C., pressure of 0.05-0.5 MPa, and pressure roller speed of 2-5 m / min.

[0034] After hot pressing, the polymer films on both sides are bonded together by chemical bonds, and cross-linking occurs inside the base film, the strength of the current collector is increased, and the tensile elongation is reduced.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] 1. In the present invention, the polymer film is modified by cross-linking modification; on the one hand, the interfacial bonding strength between the polymer film and the base layer can be ensured, which improves the strength of the composite current collector; on the other hand, the elongation of the composite current collector can be reduced, and the processing performance of the bipolar current collector can be improved.

[0037] 2. The intermediate polymer film layer of the bipolar current collector prepared by the present invention is obtained by heating, pressing, and reacting and bonding a single-sided aluminum layer-composite current collector and a single-sided copper layer-composite current collector; on the one hand, it can effectively prevent the appearance of holes in the single-layer film, thereby causing a short circuit to the positive and negative electrodes, greatly improving the safety performance of the battery; on the other hand, it can effectively eliminate the internal stress of the polymer film and prevent the curling of the pole piece.

[0038] 3. The process for preparing the bipolar current collector of the present invention is simple and economical, and has obvious advantages in product application. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 Schematic diagram of the structure of the bipolar current collector. DETAILED DESCRIPTION

[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] It should be noted that the purchasers of all raw materials involved in the present invention include, without any special restrictions, illustratively:

[0042] Polyethylene terephthalate film (PET film), with thicknesses of 10 μm, 6 μm, and 4.5 μm, model XR40H, purchased from Toray, South Korea;

[0043] Polypropylene film (PP film), thickness 4.5 μm, model XT-002-005, purchased from Wenzhou Xintai New Materials Co., Ltd.;

[0044] Diisopropylbenzene peroxide has a purity of 99%, CAS number: 80-43-3; di-tert-butyl peroxide has a purity of 99%, CAS number: 110-05-4, both of which are commercially available.

[0045] Example 1: A method for preparing a high-strength and low-elongation bipolar current collector:

[0046] S1: Preparation of single-sided aluminum layer-composite current collector:

[0047] S11. Take a 6 μm thick PET film I, immerse it in a 1 mol / L diisopropylbenzene peroxide ethanol solution, soak it at 50°C for 60 seconds, take it out, and then dry it at 80°C to obtain a modified PET film I; finally, a 5 nm thick aluminum oxide layer (base layer I) is deposited on one side of the modified PET film I by vacuum evaporation;

[0048] The process parameters of vacuum evaporation are: vacuum degree is 0.8×10 -2 Pa, evaporation temperature is 1450℃;

[0049] S12. A 1 μm thick aluminum layer is deposited on the surface of the aluminum oxide layer of the thin film obtained in S1 by vacuum evaporation to obtain a single-sided aluminum layer-composite current collector;

[0050] The process parameters of vacuum evaporation are: vacuum degree is 0.8×10 -2 Pa, evaporation temperature is 1550℃;

[0051] S2: Preparation of single-layer copper layer-composite current collector:

[0052] S21. Take a 4.5 μm thick PET film II, immerse it in a 1 mol / L diisopropylbenzene peroxide ethanol solution, soak it at 50° C. for 40 seconds, take it out, and then dry it at 80° C. to obtain a modified PET film II; finally, a 10 nm thick nickel-chromium layer (base layer II) is deposited on one side of the modified PET film II by magnetron sputtering;

[0053] The process parameters of magnetron sputtering are: vacuum degree is 0.8×10 -2 Pa, sputtering power is 1KW;

[0054] S22. A 1 μm thick copper layer is deposited on the surface of the nickel-chromium layer of the thin film obtained in S2 by water electroplating to obtain a single-sided copper layer-composite current collector;

[0055] The process parameters of water electroplating are: copper sulfate concentration is 200g / L, current density is 3A / dm 2 , voltage is 10V, temperature is 50℃;

[0056] S3: The undeposited surfaces of the single-sided aluminum layer-composite current collector obtained in S1 and the single-sided copper layer-composite current collector obtained in S2 are bonded to each other, and heated and pressed at a temperature of 120°C, a pressure of 0.2 MPa, and a roller speed of 3 m / min to obtain a high-strength and low-elongation bipolar current collector.

[0057] Example 2: A method for preparing a high-strength and low-elongation bipolar current collector:

[0058] S1: Preparation of single-sided aluminum layer-composite current collector:

[0059] S11. Take a 6 μm thick PET film I, immerse it in a 1 mol / L diisopropylbenzene peroxide ethanol solution, soak it at 30°C for 60 seconds, take it out, and then dry it at 80°C to obtain a modified PET film I; finally, a 5 nm thick aluminum oxide layer (base layer I) is deposited on one side of the modified PET film I by vacuum evaporation;

[0060] The process parameters of vacuum evaporation are: vacuum degree is 0.8×10 -2 Pa, evaporation temperature is 1450℃;

[0061] S12. A 1 μm thick aluminum layer is deposited on the surface of the aluminum oxide layer of the thin film obtained in S1 by vacuum evaporation to obtain a single-sided aluminum layer-composite current collector;

[0062] The process parameters of vacuum evaporation are: vacuum degree is 0.8×10 -2 Pa, evaporation temperature is 1550℃;

[0063] S2: Preparation of single-layer copper layer-composite current collector:

[0064] S21. Take a 4.5 μm thick PP film II, immerse it in a 1 mol / L acetone solution of di-tert-butyl peroxide, soak it at 50° C. for 40 seconds, take it out, and then dry it at 80° C. to obtain a modified PET film II; finally, a 10 nm thick nickel-chromium layer (base layer II) is deposited on one side of the modified PET film II by magnetron sputtering;

[0065] The process parameters of magnetron sputtering are: vacuum degree is 0.8×10 -2 Pa, sputtering power is 1KW;

[0066] S22. A 1 μm thick copper layer is deposited on the surface of the nickel-chromium layer of the thin film obtained in S2 by water electroplating to obtain a single-sided copper layer-composite current collector;

[0067] The process parameters of water electroplating are: copper sulfate concentration is 200g / L, current density is 3A / dm 2 , voltage is 10V, temperature is 50℃;

[0068] S3: The undeposited surfaces of the single-sided aluminum layer-composite current collector obtained in S1 and the single-sided copper layer-composite current collector obtained in S2 are bonded to each other, and heated and pressed at a temperature of 120°C, a pressure of 0.2 MPa, and a roller speed of 3 m / min to obtain a high-strength and low-elongation bipolar current collector.

[0069] Based on Example 1, a control experiment was carried out, specifically Comparative Examples 1 to 2, as described below:

[0070] Comparative Example 1: Comparative Example 1 is based on Example 1, with the following modifications: only one PET base film is used, and deposition treatment is performed on both surfaces thereof, while other processes remain unchanged, specifically:

[0071] A method for preparing a high-strength and low-elongation bipolar current collector:

[0072] S1. Take a 10 μm thick PET film, immerse it in a 1 mol / L diisopropylbenzene peroxide ethanol solution, soak it at 50°C for 60s, take it out, and then dry it at 80°C to obtain a modified PET film;

[0073] S2. A 5 nm thick aluminum oxide layer (base layer I) was deposited on one side of the modified PET film by vacuum evaporation; and a 1 μm thick aluminum layer was deposited on the surface of the aluminum oxide layer by vacuum evaporation to obtain a single-sided aluminum layer - composite current collector;

[0074] S3. A 10 nm thick nickel-chromium layer (base layer II) is deposited on the other side of the modified PET film by magnetron sputtering; and a 1 μm thick copper layer is deposited on the surface of the nickel-chromium layer by water electroplating to obtain a high-strength and low-elongation bipolar current collector;

[0075] The process parameters of vacuum evaporation are: vacuum degree is 0.8×10 -2 Pa, evaporation temperature is 1550℃;

[0076] The process parameters of magnetron sputtering are: vacuum degree is 0.8×10 -2 Pa, sputtering power is 1KW;

[0077] The process parameters of water electroplating are: copper sulfate concentration is 200g / L, current density is 3A / dm2 , voltage is 10V, temperature is 50℃;

[0078] Comparative Example 2: Comparative Example 2 is based on Example 1, with the following modifications: instead of using a heating and pressing method to bond the single-sided aluminum layer-composite current collector and the single-sided copper layer-composite current collector, a polyurethane adhesive is used to bond them together, and other processes remain unchanged, specifically:

[0079] A method for preparing a high-strength and low-elongation bipolar current collector:

[0080] S1: Preparation of single-sided aluminum layer-composite current collector:

[0081] S11. Take a 6 μm thick PET film I, immerse it in a 1 mol / L diisopropylbenzene peroxide ethanol solution, soak it at 50°C for 60 seconds, take it out, and then dry it at 80°C to obtain a modified PET film I; finally, a 5 nm thick aluminum oxide layer (base layer I) is deposited on one side of the modified PET film I by vacuum evaporation;

[0082] The process parameters of vacuum evaporation are: vacuum degree is 0.8×10 -2 Pa, evaporation temperature is 1450℃;

[0083] S12. A 1 μm thick aluminum layer is deposited on the surface of the aluminum oxide layer of the thin film obtained in S1 by vacuum evaporation to obtain a single-sided aluminum layer-composite current collector;

[0084] The process parameters of vacuum evaporation are: vacuum degree is 0.8×10 -2 Pa, evaporation temperature is 1550℃;

[0085] S2: Preparation of single-layer copper layer-composite current collector:

[0086] S21. Take a 4.5 μm thick PET film II, immerse it in a 1 mol / L diisopropylbenzene peroxide ethanol solution, soak it at 50° C. for 40 seconds, take it out, and then dry it at 80° C. to obtain a modified PET film II; finally, a 10 nm thick nickel-chromium layer (base layer II) is deposited on one side of the modified PET film II by magnetron sputtering;

[0087] The process parameters of magnetron sputtering are: vacuum degree is 0.8×10 -2 Pa, sputtering power is 1KW;

[0088] S22. A 1 μm thick copper layer is deposited on the surface of the nickel-chromium layer of the thin film obtained in S2 by water electroplating to obtain a single-sided copper layer-composite current collector;

[0089] The process parameters of water electroplating are: copper sulfate concentration is 200g / L, current density is 3A / dm 2 , voltage is 10V, temperature is 50℃;

[0090] S3: After coating the other surfaces of the single-sided aluminum layer-composite current collector obtained in S1 and the single-sided copper layer-composite current collector obtained in S2 with a polyurethane adhesive, the two are bonded together to obtain a high-strength and low-elongation bipolar current collector.

[0091] Performance test: The bipolar current collectors prepared in Examples 1 to 2 and Comparative Examples 1 to 2 were subjected to relevant performance tests, as follows:

[0092] (1) The tensile strength and elongation of the bipolar current collector were tested according to the standard of GB / T 1040.3-2006;

[0093] (2) The bipolar current collector was baked at 150°C for 30 min and then subjected to a thermal shrinkage test;

[0094] (3) Conduct density transmittance test on the bipolar current collector.

[0095] (4) Cut the bipolar current collector into a size of 10 cm × 10 cm, place it naturally on a flat table, and measure the maximum height of the bipolar current collector edge warping;

[0096] The specific test results are shown in Table 1 below:

[0097] Table 1

[0098]

[0099]

[0100] Result analysis: It can be seen from the data in the above table that the tensile strength, elongation and thermal shrinkage of the bipolar current collector prepared by the present invention are far superior to those of the bipolar current collector prepared by the traditional method, and there is no risk of light transmission, the internal stress of the material is smaller, and the warping is also smaller.

[0101] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing a high-strength and low-elongation bipolar current collector, characterized in that: The specific steps include: S1: Preparation of single-sided aluminum layer-composite current collector: S11. A layer of a base layer I is deposited on one side of the polymer film I by a physical deposition method; S12. A layer of aluminum is deposited on the surface of the base layer I by vacuum evaporation to obtain a single-sided aluminum layer - composite current collector; S2: Preparation of single-layer copper layer-composite current collector: S21. Depositing a layer of bottom layer II on one side of the polymer film II by a physical deposition method; S22. A copper layer is deposited on the surface of the base layer II by water electroplating to obtain a single-sided copper layer-composite current collector; S3: The surfaces of the single-sided aluminum layer-composite current collector and the single-sided copper layer-composite current collector that have not been deposited are bonded to each other, and the surfaces are heated and pressed to obtain a high-strength and low-elongation bipolar current collector.

2. The method for preparing a high-strength and low-elongation bipolar current collector according to claim 1, characterized in that: Before the physical deposition of the polymer film I and the polymer film II, both are first subjected to cross-linking modification treatment; The cross-linking modification treatment method is: immersing the polymer film I and / or polymer II in an organic solution of a cross-linking agent, immersing for 15 to 90 seconds at 20 to 60° C., taking out, and drying to complete the cross-linking modification treatment.

3. The method for preparing a high-strength and low-elongation bipolar current collector according to claim 2, characterized in that: The polymer film I and the polymer film II include any one of polypropylene film, polyethylene film, polyethylene terephthalate film, polyimide film, polyphenylene sulfide film, and polystyrene film, and the thickness thereof is 3 to 20 μm; The crosslinking agent is a low-temperature crosslinking agent, specifically including any one of an organic peroxide crosslinking agent and a multifunctional acrylate crosslinking agent.

4. The method for preparing a high-strength and low-elongation bipolar current collector according to claim 3, characterized in that: The organic peroxide crosslinking agent includes dicumyl peroxide and di-tert-butyl peroxide; the multifunctional acrylate crosslinking agent includes trimethylolpropane triacrylate.

5. The method for preparing a high-strength and low-elongation bipolar current collector according to claim 2, characterized in that: The film parameters used for the polymer film II and the polymer film I as well as the cross-linking agent used for the cross-linking modification treatment may be different.

6. The method for preparing a high-strength and low-elongation bipolar current collector according to claim 1, characterized in that: In the present invention, the physical deposition method includes any one of magnetron sputtering and vacuum evaporation; if the physical deposition method is magnetron sputtering, the process parameters of the magnetron sputtering are: vacuum degree ≤ 1×10 -2 Pa, sputtering power is 0.5~2KW; If the physical deposition method is vacuum evaporation, the process parameters of the vacuum evaporation are: vacuum degree ≤ 1×10 -2 Pa, the evaporation temperature is 1400~1600℃.

7. The method for preparing a high-strength and low-elongation bipolar current collector according to claim 1, characterized in that: The material of the bottom layer I is metal or metal oxide, specifically including any one of aluminum oxide, chromium oxide, and chromium, and its thickness is 1 to 20 nm; the material of the bottom layer II is metal, specifically including one or a combination of nickel, chromium, and copper, and its thickness is 5 to 40 nm.

8. The method for preparing a high-strength and low-elongation bipolar current collector according to claim 1, characterized in that: The process parameters of the vacuum evaporation are: vacuum degree ≤ 1×10 -2 Pa, evaporation temperature is 1400-1600°C; the thickness of the aluminum layer is 0.5-2 μm; the process parameters of the water electroplating are: copper sulfate concentration is 180-220 g / L, current density is 2.5-3.5 A / dm 2 , the voltage is 8-12V, the temperature is 45-55°C; the thickness of the copper layer is 0.5-2μm.

9. The method for preparing a high-strength and low-elongation bipolar current collector according to claim 1, characterized in that: The process parameters of the heating and pressing are: temperature of 60-150° C., pressure of 0.05-0.5 MPa, and pressure roller speed of 2-5 m / min.

10. A high-strength and low-elongation bipolar current collector prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The high-strength and low-elongation bipolar current collector is sequentially arranged to include: an aluminum layer, a base layer I, a polymer film layer, a base layer II, and a copper layer.

Citation Information

Patent Citations

  • Low-swelling composite current collector and preparation method thereof

    CN114864953A

  • Composite copper current collector and preparation method and application thereof

    CN115133039A

  • Composite current collector and preparation method and application thereof

    CN116072883A

  • Bipolar current collector, preparation method thereof, bipolar electrode and lithium battery

    CN116565213A

  • High-strength positive electrode based on polymer graft modification as well as preparation method and application of high-strength positive electrode

    CN116825970A